Designing ICT Competences-Integrated Lesson Planning Course Teaching Model for English Language Education - Nurpratiwi, Fheby Indriyanti (Journal of Literature Language and Academic Studies, 2024)
This study aims at designing ICT Competences-Integrated Lesson Planning Course Teaching Model for English Language Education. This study employed a modified Design and Development Research (DDR) model from Borg, R.W. & Gall (2007) and Ellis & Levy (2010) that consist of four procedures namely need analysis, preliminary prototype design, evaluation and design revision. There were two existing teaching models collected from classroom observation and four documents of lesson planning course collected from four universities in Indonesia was analyzed by using ICT Competences frameworks of UNESCO and other ICT competences theories. The results of analysis revealed that the existing teaching model of the course mostly and implicitly integrated ICT competences into teaching method and technique. The most applied level of ICT competences in the existing models of teaching was Technology Literacy. The proposed models of teaching designed ICT competences into approaches, method and technique by providing six integration procedures. The newly designed teaching model accommodated the necessary ICT Competences in all levels namely Technology Literacy, Knowledge Deepening and Knowledge Creation as well as applied the three approaches of Cognitive, Humanistic and Behavioral approach modified with Scaffolding, Project-based Learning and Computer Assisted Instruction method for lesson planning course teaching model design.